South Africa’s migration policy mess: Where did it come from, and can it be fixed? - Hirsch, Alan (New Agenda: South African Journal of Social and Economic Policy, 2024)
Alan Hirsch comments on the draft White Paper on Citizenship, Immigration and Refugee Protection issued by the South African government in November 2023. The government wants to make laws still tighter when it is unable to implement existing laws. He finds that what is proposed simply won’t help and suggests what could be done to fix the urgent need for better migration policy.